Why Noncompliance - Börzel, Tanja A. (Cornell University Press, 2021)
Why Noncompliance traces the history of noncompliance within the European Union (EU), focusing on which states continuously do or do not follow EU Law, why, and how that affects the governance in the EU and beyond. n exploring the EU's long and varied history of noncompliance, Tanja A. Börzel takes a close look at the diverse groups of noncompliant states throughout the EU's existence. Why do states that are vocally critical of the EU have a better record of compliance than those that support the EU? Why has noncompliance been declining since the 1990s, even though the EU was adding member-states and numerous laws? Börzel debunks conventional wisdoms in EU compliance research, showing that noncompliance in the EU is not caused by the new Central and Eastern European member states, nor by the Eurosceptic member states. So why do these states take the brunt of Europe's misplaced ire? Why Noncompliance introduces politicization as an explanatory factor that has been long overlooked in the literature and scholarship surrounding the European Union. Börzel argues that political controversy combined with voting power and administrative capacity, explains why noncompliance with EU law has been declining since the completion of the Single Market, cannot be blamed on the EU's Central and Easter European member states, and is concentrated in areas where EU seeks to protect citizen rights.